2019 IEEE International Conference on Healthcare Informatics (ICHI) 2019
DOI: 10.1109/ichi.2019.8904554
|View full text |Cite
|
Sign up to set email alerts
|

Towards Device-Agnostic Mobile Cough Detection with Convolutional Neural Networks

Abstract: Ubiquitous mobile devices have the potential to reduce the financial burden of healthcare systems by providing scalable and cost-efficient health monitoring applications. Coughing is a symptom associated with prevalent pulmonary diseases, and bears great potential for being exploited by monitoring applications. Prior research has shown the feasibility of cough detection by smartphone-based audio recordings, but it is still open as to whether current detection models generalize well to a variety of mobile devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 39 publications
0
57
0
1
Order By: Relevance
“…This work was built upon a convolutional neural network architecture for cough recognition that we introduced in previous work [ 32 ] which recognized coughs in Mel spectrograms. Mel-scaled spectrograms are visual representations of audio signals with respect to time and frequency.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This work was built upon a convolutional neural network architecture for cough recognition that we introduced in previous work [ 32 ] which recognized coughs in Mel spectrograms. Mel-scaled spectrograms are visual representations of audio signals with respect to time and frequency.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed calculation of the Mel spectrograms used can be found in Multimedia Appendix 1 . We evaluated this approach against different approaches for smartphone-based cough recognition in previous work on voluntary coughs and found that it performed best [ 32 ]. Our approach produced stable results across recordings of five different devices with different hardware and service life duration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To maximize the information that can be derived from a one-second sound, we propose a Convolutional Neural Network (CNN). CNNs have already been successfully applied to different audio event detection applications [1,5,63,83]. For BEM to identify breath sound, we employ a single layer CNN to extract information from the entire one-second sound features.…”
Section: Breathing Phases Detection Modulementioning
confidence: 99%